2022
DOI: 10.1186/s43014-022-00096-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying cereal/legume intercropping as nature-based biofortification: A review

Abstract: The deficiencies of micronutrients known as hidden hunger are severely affecting more than one-half of the world’s population, which is highly related to low bioavailability of micronutrients, poor quality diets, and consumption of cereal-based foods in developing countries. Although numerous experiments proved biofortification as a paramount approach for improving hidden hunger around the world, its effectiveness is highly related to various soil factors, climate conditions, and the adoption rates of bioforti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 135 publications
1
7
0
Order By: Relevance
“…Below-ground complementarity, nutrient sharing via interspecific root interactions, and rhizosphere modification in maize-soybean intercropping could also impact crop growth, development, and yield, either directly or indirectly [ 26 , 53 ]. Adequate N fertilization could further increase the yield of crops under such intercropping system where N is a primary element required for plant growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Below-ground complementarity, nutrient sharing via interspecific root interactions, and rhizosphere modification in maize-soybean intercropping could also impact crop growth, development, and yield, either directly or indirectly [ 26 , 53 ]. Adequate N fertilization could further increase the yield of crops under such intercropping system where N is a primary element required for plant growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Below-ground complementarity, nutrient sharing via interspeci c root interactions, and rhizosphere modi cation in maize-soybean intercropping could also impact crop growth, development, and yield, either directly or indirectly [26,53]. Adequate N fertilization could further increase the yield of crops under such intercropping system where N is a primary element required for plant growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, maize-common bean intercropping considerably enhanced the maize crop yield by 12.5% and biomass dry matter (shoots and root) by 31.5% when compared with its mono-cropping system [61]. Several other intercropping studies have shown that the complementarity or facilitative interactions that occur both above and below ground between intercrops consequently improve the soil nutrient availability and increase plant nutrient content and their uptake, which ultimately enhances the crop yield [53,62,63], and that con rmed our results.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the ongoing discussion on the post-2020 European Common Agricultural Policy, and the current sustainability agenda (e.g., Paris Climate Agreement, European Strategy of Biodiversity and the European Mission of Soil, Sustainable Development Goals), there is a need to promote sustainable agricultural management practices that contribute to SOC sequestration while reducing external inputs such as fertilizers and pesticides (Pe'Er et al, 2019). In this regard, crop diversification (either adding more crops into an existing crop rotation scheme or inter-cropping, i.e., growing annual or perennial crops in the inter-tree-rows of woody crops) is a promising strategy to mitigate climate change and land degradation through soil carbon sequestration while ensuring food security and maintaining natural resources (soil, water and biodiversity), particularly in dry regions (Francaviglia et al, 2017;Sanz et al, 2017;Yang et al, 2021;Ebbisa, 2022).…”
Section: Introductionmentioning
confidence: 99%